Immature platelets as a novel biomarker for adverse cardiovascular events in patients after non-cardiac surgery - Anetsberger, Aida; Blobner, Manfred; Haller, Bernhard; Schmid, Sebastian; Umgelter, Katrin; Hager, Theresa; Langgartner, Clemens; Kochs, Eberhard F.; Laugwitz, Karl-Ludwig; Jungwirth, Bettina; Bernlochner, Isabell (Thrombosis and Haemostasis, 2017)
This study evaluates whether immature platelets (IPF) determined in the post anesthesia care unit (PACU) can predict major adverse cardiovascular events (MACE) or other thromboembolic events after intermediate and high-risk surgery. IPF are increased in patients with acute coronary syndrome and recently gained interest as novel biomarker for risk stratification. In this prospective observational trial 732 patients undergoing intermediate or high-risk non-cardiac surgery were enrolled (NCT02097602). IPF was measured preoperatively and postoperatively in the PACU. Primary outcome was a composite endpoint defined as MACE, deep vein thrombosis or pulmonary embolism during hospital stay (modMACE). A cut off for IPF identifying a threshold between a low and high risk for modMACE was calculated by logrank optimization. A multivariate Cox regression was calculated in a forward stepwise manner to assess the relation between this IPF cut off and modMACE as well as other established risk factors (inclusion if p<0.05). Preoperatively, there were no differences in IPF between patients with and without modMACE (3.1% [2.2% – 4.7%](median [interquartile range]) vs. 2.8% [1.9% – 4.3%]. Patients with modMACE (28 of 730 patients; 3.8%) had higher IPF values in the PACU compared to patients without modMACE (3.6% [2.6–6%] vs. 2.9% [2–4.4%]; p=0.011). The optimal cut off of IPF > 5.4% was associated with an increased risk for modMACE after adjustment for covariates (hazard ratio: 2.528; 95% confidence interval: 1.156 to 5.528, p=0.02). In conclusion, IPF is an independent predictor of modMACE after surgery and might improve risk stratification of surgical patients.Institution where the work was performed and funded: Klinikum rechts der Isar der Technischen Universität München, Ismaningerstr. 22, 81675 Munich, Germany.
Keywords: Reticulated platelets; immature platelet fraction; non-cardiac surgery; major adverse events; thrombotic events